Long term follow-up of a phase II trial of multimodal therapy given in a “sandwich” method for stage III, IV, and recurrent endometrial cancer - Glasgow, Michelle (Gynecol Oncol Res Pract, 2016)
BACKGROUND: Our objective was to determine if previously reported overall survival (OS) and progression-free survival (PFS) rates are maintained long term following multimodal therapy for advanced and recurrent endometrial cancer and to assess the lymphedema rates associated with this therapy. METHODS: Women with advanced-stage or recurrent endometrial cancer were recruited between 9/2004 and 6/2009 to our previously published Phase II trial. Patients received intravenous docetaxel (75 mg/m2) and carboplatin (AUC = 6) every 3 weeks for 3 cycles before and after radiation therapy. Patient outcomes were updated in July 2014. Data abstracted included presence of lymphedema, disease progression, and death. OS and PFS estimates at 5 years were calculated using Kaplan-Meier methods. RESULTS: Of the 41 patients enrolled, 10 (24 %) had stage IIIA and 21 (51 %) had stage IIIC disease; 32 (78 %) had endometrioid histology; and 35 (85 %) completed the protocol. With a median follow-up of 5 years, 15 of 41 patients have died. The Kaplan–Meier estimate and 95 % CI for OS at 5 years was 70 % (53–82 %). Excluding the two patients with recurrent disease at enrollment, 15 of 39 patients progressed or died during follow-up. The Kaplan–Meier estimate and 95 % CI for PFS at 5 years was 66 % (48–78 %). Fifteen patients (37 %) had medical record documentation of lymphedema following treatment. CONCLUSIONS: After additional follow-up, OS and PFS estimates remain high and in-field recurrences low following “sandwich” therapy. The “sandwich” method remains efficacious for women with stage III-IV or recurrent endometrial cancer.